Sintesis dan Karakterisasi Pigmen Merah Hematit (α-Fe2O3) dari Pasir Besi Kabupaten Sijunjung, Sumatera Barat, Indonesia - Ahmad Fajri Soekansa; Nafis Sudirman; Syamsi Aini (Departemen Kimia FMIPA UNP, 2023)
Hematite red pigment has been successfully synthesized from natural iron sand originating from the Sijunjung area, West Sumatra, Indonesia. The purified natural iron sand contains magnetic dioxide particles to produce ferric ions (Fe3+) which can be used as precursors for the synthesis of the red pigment hematite. Hematite red pigment synthesis was carried out by coprecipitation method with NaOH precipitating agent. The red pigment hematite was synthesized by varying the mass solubility of 1 g, 1.5 g, and 2 g which were reacted with 4 M, 5 M, and 6 M HCl to produce a precursor with the highest ferric ion solubility. The precursor with the highest ferric ion solubility was formed from the reaction between 1 g of pure iron sand and 6 M HCl. The second variation was the increase in calcination temperature, namely 650oC, 700 oC, 750oC, and 800oC, with a calcination temperature of 800oC producing the brightest red pigment hematite. The higher the calcination temperature causes an increase in the brightness of the synthetic red pigment hematite. The characterization was carried out using XRD to see the crystal structure of the product and UV-Vis to see the absorption wavelength.